Integrating Maternal Infant & Young Child Nutrition (MIYCN) in Undergraduate Medical Teaching Curriculum and Service Delivery in Two States of India (P04-162-19). (13th June 2019) - Ghosh, Sebanti
Abstract: Objectives: Medical colleges play an important role in creating future generations of well-trained practitioners through their teaching, services and research. In India, as part of provision of technical assistance to government & partner organizations at national & state level for strengthening MIYCN policy/programming, A&T is working with 8 selected medical colleges in Uttar Pradesh and Bihar to develop an evidence-based model, for assessing extent to which MIYCN can be addressed in the undergraduate curricula and MIYCN interventions included in the service delivery. Methods: Quantitative pre (2017) and post (2019) cross-sectional survey design Based on baseline assessment findings, an intervention plan for integrating MIYCN content in undergraduate medical curricula and updating MIYCN service delivery protocols developed and currently under implementation in 8 pre-selected national medical colleges in states of Uttar Pradesh and Bihar in India. Midline process review of key milestones undertaken in 2018 Results: During baseline, 60% of the faculty stated that maternal nutrition topics are not adequately covered and half of them said that IYCF topics not adequately covered in curriculum. Knowledge & availability of standard MIYCN protocols remained low, between 20–30%, resulting in suboptimal service delivery. Midline review shows the following processes successfully being put in place to address the gaps identified in the baseline: Development of enhanced curriculum focusing on MIYCN topics and updated standard protocols for MIYCN service delivery Interdepartmental coordination committees for ensuring roll-out of enhanced curriculum and updated protocol. Conclusions: Crucial factors that contributed to current positive outcomes are i) involving medical colleges in leading and delivering key interventions ii) ensuring ownership of state government and, iii) inclusion of MIYCN topics into the existing undergraduate medical curriculum to facilitate adoption and adaptation across India. Funding Sources: The initiative is funded by the Bill & Melinda Gates Foundation.